Comparison between preoperative computed tomography scan of paranasal sinuses and operative findings in functional endoscopic sinus surgery (FESS) in chronic sinusitis - Kumari, Amita; Kaur, Amarjit; Mathur, Manoj; Singh, Jasvir; Kaur Mohi, Jaswinder; Haq, Samrin (International Journal of Medical Research and Review, 2016)
Background and objectives: The study was done to evaluate the role of computed tomography (CT) in clinically suspected cases of chronic sinusitis for detection, assessment of anatomical variants and pathological abnormalities of nasal cavity and paranasal sinuses. Also findings of CT were co-related with operative findings in functional endoscopic sinus surgery (FESS). The study was conducted on 60 cases attending CT section of Radiodiagnosis Department and ENT Department Rajindra Hospital, Patiala. Materials and Methods: The study was conducted on 60 cases over a period 3 years from 2010 to 2013 irrespective of gender and age group attending the ENT and radiology department. Selections of patients were based on clinical features like nasal or post nasal discharge, nasal obstruction, headache anosmia, cough and hoarseness of voice. Relevant history, clinical examination and CT examination of every patient were done. Results: In our study, the CT scan and operative findings correlated excellently in cases of paradoxical middle turbinate, bony destruction, concha bullosa, polypoidal changes in ethmoidal sinuses and osteomeatal complex normal widening. There was very good agreement between preoperative CT scan and operative findings for concha bullosa, paradoxical middle turbinate, bony destruction, osteomeatal complex normal widening, polypoidal change in sphenoid sinus. The most common pattern observed on CT scan was osteomeatal unit pattern in 35% followed by infundibular pattern (20%), sphenoethmoidal recess pattern (23.3%), unclassified pattern (15%) & sinonasal polyposis pattern (6.6%). Conclusion: CT is the imaging modality of choice to reveal mucosal changes deeper in osteomeatal complex which are not visible endoscopically and to identify extent of paranasal sinus disease. However, endoscopy has complementary role with CT in evaluation of patients of chronic sinusitis.